2015
DOI: 10.1242/dev.113894
|View full text |Cite
|
Sign up to set email alerts
|

Glypican4 promotes cardiac specification and differentiation by attenuating canonical Wnt and Bmp signaling

Abstract: Glypicans are heparan sulphate proteoglycans (HSPGs) attached to the cell membrane by a glycosylphosphatidylinositol (GPI) anchor, and interact with various extracellular growth factors and receptors. The Drosophila division abnormal delayed (dally) was the first glypican lossof-function mutant described that displays disrupted cell divisions in the eye and morphological defects in the wing. In human, as in most vertebrates, six glypican-encoding genes have been identified (GPC1-6), and mutations in several gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 82 publications
0
36
0
2
Order By: Relevance
“…Recently, it was shown that, in the pLLP, Gpc4 affects the expression of sonic hedgehog (Shh) during the development of muscle cells, which express the chemokine that directs LLP migration (Venero Galanternik et al, 2016). Similarly, Gpc4 regulates the specification and differentiation of cardiac mesoderm by attenuating Wnt and Bmp signaling in the anterior lateral plate mesoderm where cardiac cells are located (Strate et al, 2015). In the zebrafish gastrula, gpc4 is expressed ubiquitously (Topczewski et al, 2001).…”
Section: The Role Of Wnt/pcp Signaling In Endoderm Migrationmentioning
confidence: 99%
“…Recently, it was shown that, in the pLLP, Gpc4 affects the expression of sonic hedgehog (Shh) during the development of muscle cells, which express the chemokine that directs LLP migration (Venero Galanternik et al, 2016). Similarly, Gpc4 regulates the specification and differentiation of cardiac mesoderm by attenuating Wnt and Bmp signaling in the anterior lateral plate mesoderm where cardiac cells are located (Strate et al, 2015). In the zebrafish gastrula, gpc4 is expressed ubiquitously (Topczewski et al, 2001).…”
Section: The Role Of Wnt/pcp Signaling In Endoderm Migrationmentioning
confidence: 99%
“…Both glypican-1 and -3 also bind BMP-2 and block BMP-2 signaling in cranial osteogenesis (Dwivedi et al 2013). In zebrafish, glypican-4 attenuates BMP signaling to regulate cardiac development (Strate et al 2015). As glypicans also regulate Wnt, hedgehog, and FGF signaling (Bernfield et al 1999;Lin and Perrimon 2000;Fico et al 2011), the six vertebrate glypicans may differentially modulate overlapping and distinct signaling pathways during vertebrate embryogenesis and homeostasis.…”
Section: Glypicansmentioning
confidence: 99%
“…The following lines were used in this study: wild-type AB, desma ct122Gta and desma ct122aRGt lines (Trinh et al, 2011), desma sa5 (Kettleborough et al, 2013), Tg(myl7:egfp) (Huang et al, 2003), Tg(myl7:ras-eGFP) s883 (D'Amico et al, 2007), Tg(fli1a:neGFP) y7 (Roman et al, 2002), Tg(fli:gal4FF ubs ; UAS:kaede) (Herwig et al, 2011), Tg(myl7:GalFF; UAS:RFP) hu6228 (Strate et al, 2015), and Tg(UAS:gcamp3.0; Gal4s1020t) (Warp et al, 2012) and were described previously. Embryos were staged according to hours (hpf) and days postfertilization (dpf).…”
Section: Zebrafish Husbandry and Embryo Treatmentsmentioning
confidence: 99%